2022
DOI: 10.3389/fpsyt.2022.803959
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Temperament as a Factor of Risk and Protection for Later Childhood Psychopathology

Abstract: BackgroundTemperament might be considered as a risk factor as well as a resilience factor for later externalizing and internalizing disorders. Therefore, this study examines different dimensions of temperament in preschool age with regard to their predictive value for psychopathology later in childhood.MethodsA total of 76 patients (63.2% male) were assessed in a special psychiatric consultation for preschool age at measuring point time t1 (x = 4.2) and measuring point time t2 (x = 9.2). At t1, the Integrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…If child temperament is a risk factor for ECC, then education and other health professionals may play a role in identifying and referring preschool children to proper care services; thus, this highlights the importance of the involvement of paediatric primary carers with oral healthcare professionals in the prevention of ECC. When planning oral healthcare strategies for preschool children, it is recommended to consider psychological characteristics and the identification of personality traits which might serve as predictive behaviours during dental visits [ 37 , 38 ] and of later psychopathology [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…If child temperament is a risk factor for ECC, then education and other health professionals may play a role in identifying and referring preschool children to proper care services; thus, this highlights the importance of the involvement of paediatric primary carers with oral healthcare professionals in the prevention of ECC. When planning oral healthcare strategies for preschool children, it is recommended to consider psychological characteristics and the identification of personality traits which might serve as predictive behaviours during dental visits [ 37 , 38 ] and of later psychopathology [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies have shown that parent-reported difficult temperament in infancy and toddlerhood is associated with greater psychopathology in childhood and adolescence, greater depression, lower wellbeing, and unemployment in adulthood. [10][11][12][13][14][15] Children with difficult temperaments often struggle to regulate their emotions and behaviors, which can lead to difficulties in forming and maintaining positive relationships with peers, teachers, and family members. Over time, these interpersonal challenges can contribute to social withdrawal, loneliness, and even social rejection, which may persist into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, these interpersonal challenges can contribute to social withdrawal, loneliness, and even social rejection, which may persist into adulthood. [10][11][12][13][14][15] Furthermore, difficult temperament in childhood is associated with an increased risk of developing internalizing and externalizing problems such as anxiety, depression, and conduct disorder. These mental health difficulties can have long-term consequences for individuals' educational attainment, employment prospects, and overall well-being in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Parental reports are often used to measure child temperament due to the unsuitability of self-report in young children and the costs and poor reliability of child observations (9). A parent reported di cult temperament in infancy and toddlerhood is associated with greater psychopathology in childhood and adolescence and greater depression, lower wellbeing, and unemployment in adulthood (10)(11)(12)(13)(14)(15). Understanding the current prevalence of di cult temperament and associated risk factors is important for early identi cation and targeted interventions (10).…”
Section: Introductionmentioning
confidence: 99%